Assessing oxidative, inflammatory and serotonergic pathways of coenzyme Q10 on anxiety and depression-like behavior caused by abstinence following co-administration of ethanol and nicotine in adolescent Wistar male rats - Mobina Mahdizadeh; Samaneh Kakhki; Seyed Pouria Tafti; Seyed Amirsadra Khatibi; Fatemeh Kaffashan; Farimah Beheshti (Heliyon)
Background: The present study aims to assess the potential effect of coenzyme Q10 (CoQ10) on anxiety and depressive-like behavior associated with withdrawal following concurrent usage of ethanol (Eth) and nicotine (Nic) in adolescent male rats. Method and materials: The adolescent male rats were accidently assigned into 7 groups: 1) vehicle, 2) Nic-Eth (Nic 2 mg/kg and cumulative dose of Eth (started from 5 % to reach 20 % gradually, from 21 till 42 days of ages), 3–5) Nic-Eth Q10100/200/400 mg/kg (received Nic-Eth and received CoQ10 at three different doses by oral gavage, 43–63 days of ages), 6) Nic-Eth-Bup-Nal (received Nic-Eth and received Bupropion (20 mg/kg) and naloxone (10 mg/kg) at 43–63 days of ages, and 7) received normal saline from 21 to 42 days of age after that received CoQ10 400 mg/kg from 43 to 63 days of ages. Eventually, both behavioral and biochemical analysis related to anxiety and depression were performed. Results: Considering the present findings, CoQ10 attenuated the anxiety-depressive like behavior associated with withdrawal following concurrent use of Nic and Eth by behavioral analysis. CoQ10 at the highest doses (400 mg/kg) balanced oxidant/anti-oxidant as well as pro-inflammatory/anti-inflammatory mediators in addition to increase of serotonin level, and decrease of monoamine oxidase (MAO) in cortical tissue. It is outstanding that the highest dose of CoQ10 illustrated much better results than other doses as well as Bup-Nal, as standard medications approved for withdrawal caused by Nic, and Eth. Conclusion: The present findings in lines with prior studies confirmed anti-oxidant and anti-inflammatory effect of CoQ10. Also, the results demonstrated positive effect on serotonin as important neurotransmitter responsible for mood stability.